Open source geographic information systems: promoting access to health services information through a local and participatory development methodology - Ricketts, Adam (Department of Civil Engineering, 2024)
The challenges associated with the provision of health services in South Africa are immense. The South African Government aims to address some of these challenges through the decentralisation of health services management. Information sharing and dissemination is seen as a critical factor in the success of such a structure. Geographic information systems (GIS) have been identified as a means through which information can be shared. The research aims to determine how GIS can aid the management of health related services through the use and sharing of information. This is based on the premise that the GIS is developed in a participatory manner and focused at the local community level. Three major steps make up the research being presented. The first aimed to determine the status quo of GIS use in South Africa. An online questionnaire was designed for this purpose. The second was the facilitation of the participatory development of an open source GIS prototype based on the results of the online questionnaire. The third step was the testing of the GIS prototype. Testing was completed using methodologies from case study research and human computer interaction (HCI), and included a case study of the Overstrand municipal area, in which usability testing of the GIS prototype was completed. The research found that GIS has a significant role to play in the sharing and use of information at a local community level. The methodology employed in the research illustrated an effective manner in which to promote participation in the development of a system. Furthermore it was determined that open source software allows for the flexibility required for such system development, in that the focus of development must be for a specific group of people, and for specific tasks to be carried out by those people.